2013
DOI: 10.1007/s00296-013-2742-z
|View full text |Cite
|
Sign up to set email alerts
|

Is low-level laser therapy in relieving neck pain effective? Systematic review and meta-analysis

Abstract: The aim of this study is to determine the efficacy of low-level laser therapy (LLLT) in reducing acute and chronic neck pain as measured by the visual analog scale (VAS). A systematic search of nine electronic databases was conducted to identify original articles. For study selection, two reviewers independently assessed titles, abstracts, and full text for eligibility. Methodological quality was assessed using the Detsky scale. Data were analyzed using random-effects model in the presence of heterogeneity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Also, for those with shoulder and/or neck pain, evidence suggests ultrasound does not confer significant or added benefit over placebo or other treatments [47, 55, 101, 140, 153, 157]. The evidence on effectiveness of laser therapy for shoulder pain [59, 159], or acute or chronic neck pain was inconclusive [151]. With regards to knee pain, other treatments including ultrasound, electromagnetic fields, low level laser therapy, TENS, biofeedback, neuromuscular electrical stimulation may confer added benefits to exercise and / or surgical treatment but empirical and clinical effect sizes are small and only supported by weak evidence [16, 47, 48, 112, 129, 143, 146, 147].…”
Section: Resultsmentioning
confidence: 99%
“…Also, for those with shoulder and/or neck pain, evidence suggests ultrasound does not confer significant or added benefit over placebo or other treatments [47, 55, 101, 140, 153, 157]. The evidence on effectiveness of laser therapy for shoulder pain [59, 159], or acute or chronic neck pain was inconclusive [151]. With regards to knee pain, other treatments including ultrasound, electromagnetic fields, low level laser therapy, TENS, biofeedback, neuromuscular electrical stimulation may confer added benefits to exercise and / or surgical treatment but empirical and clinical effect sizes are small and only supported by weak evidence [16, 47, 48, 112, 129, 143, 146, 147].…”
Section: Resultsmentioning
confidence: 99%
“…However, this meta-analysis has been criticized for betweenstudy heterogeneity and publication bias [17,18]. In a recent review, Kadhim-Saleh et al [19] stated that their findings provide inconclusive evidence of the benefits of LLLT in patients with cervical MPS because of significant betweenstudy heterogeneity and a potential risk of bias. LLLT, also known as "low-energy" or "low-power" laser therapy, is performed at low radiation intensities.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent review 42 , the authors stated that LLLT has only short-term benefits (versus sham) in treating rotator cuff disease; however, HILT was effective in minimizing pain and disability and increasing range of motion in patients with shoulder pain 108 . Similarly, in a 2013 systematic review of LLLT in treating chronic neck pain, the authors reported that although the benefits observed were statistically significant, the differences failed to achieve a “minimally-important clinical difference” 109 . In contrast, Alayat et al found that HILT combined with exercise in patients with chronic low back 110 and neck 111 pain was more effective than exercise therapy alone and also had a more sustained effect in decreasing pain and functional disability (for example, improving range of motion), and beneficial effects lasted for up to 3 months.…”
Section: Laser Therapymentioning
confidence: 99%